Manajemen Inovasi Pendidikan Berbasis Digitalisasi Sekolah - Puput Puspito Rini (STAI Darul Qalam Tangerang, 2025)
Educational innovation management is a strategic field of study at the intersection of management, pedagogy, and technology that includes systematic efforts to plan, implement, and evaluate changes in the education ecosystem to produce globally competitive graduates. This study aims to examine the management of educational innovation based on school digitalization through four dimensions, namely the effectiveness of digital transformation, the role of artificial intelligence and algorithmic technology, the development of the digital capacity of teachers, and the influence of open innovation policies on the success of education digitalization.